Legal Review Of Death Penalty Sanctions And Asset Forfeiture In Corruption Crimes Reviewed From The Perspective Of Justice - Kusnadi, Sukamto (International Journal Of Humanities Education and Social Sciences (IJHESS), 2024)
The crime of corruption in Indonesia is regulated by Law Number 31 Year 1999 on the Eradication of Corruption, which was later updated by Law Number 20 Year 2001. This research aims to legally discuss the application of death penalty and asset forfeiture in corruption cases, by considering the principle of justice. The research uses a normative juridical method, in which data is collected from various applicable legal regulations, and the results are presented descriptively-analytically. Although the death penalty is regulated in Indonesian positive law, until now its implementation in corruption cases has never been realized. As a result, the applicable law has not fully provided an adequate sense of justice for the state and the people harmed by acts of corruption. On the other hand, the Asset Forfeiture Bill (RUU) as an effort to recover state losses has been proposed. Asset forfeiture as an additional criminal offense is already regulated in Article 10 letter (b) of the Criminal Code. While the death penalty is the main punishment, both have different implementation procedures, but both aim to realize justice. Both the death penalty and asset forfeiture are expected to have a deterrent effect on perpetrators of corruption and reduce the number of corruption crimes in Indonesia.